Ab-initio Calculations of Electronic, Transport, and Bulk Properties of cubic Boron Nitride (zb-BN) - Stewart, Anthony Duane (JOURNAL OF ADVANCES IN PHYSICS, 2015)
We present results from ab-initio, self consistent, local density approximation (LDA) calculations of electronic and related properties of cubic boron nitride (zb-BN). We employed the Ceperley and Alder LDA potential and the linear combination of atomic orbitals (LCAO) formalism in our non-relativistic computations. We solved the system of LDA equations self-consistently, through the implementation of the LCAO formalism, following the Bagayoko, Zhao, and Williams (BZW) method as enhanced by Ekuma and Franklin (BZW-EF). The BZW-EF method includes a methodical search for the optimal basis set that yields the absolute minima of the occupied energies. This search entails increasing the size of the basis set and the related modifications of angular symmetry and of radial orbitals. Our calculated, indirect band gap of 6.48 eV, from the ? to the ? points, and bulk modulus of 375 GPa are in excellent agreement with corresponding experimental values at room temperature (RT). The calculated widths of the lowest valance band and that of the entire valence bands of 5.65 eV and 20.26 eV are in excellent agreement with the measured values of 5.5 eV and 20 eV, respectively. We have also calculated electron and hole effective masses for zb-BN, and the total (DOS) and partial (pDOS) densities of states.